Accuracy evaluation of the C. elegans cancer test (N-NOSE) using a new combined method. (2021) - Inaba, Satoshi; Shimozono, Naoki; Yabuki, Hidehiko; Enomoto, Motoki; Morishita, Masayo; Hirotsu, Takaaki; di Luccio, Eric
Highlights: N-NOSE is a new, highly sensitive, non-invasive, and inexpensive cancer screening. Two 10- and 100-fold dilutions of urine improve the N-NOSE method. A new combined method increased the sensitivity up to 87.5% of N-NOSE. N-NOSE has a higher sensitivity than widely used tumor markers in cancer detection. No significant relationships of other background factors with N-NOSE index. Abstract: Early cancer detection is critical for effective treatment. N-NOSE (Nematode-NOSE) is a simple, inexpensive, and highly sensitive cancer screening method based on the chemotaxis of the nematode Caenorhabditis elegans, which shows evasive action from the urine of healthy individuals while being attracted to the urine of cancer patients. Initially, N-NOSE relied on chemotaxis indexes obtained with 10-fold dilutions of urine samples. However, cancer tissue size and concentrations of cancer odors differ among cancer patients. In this study, we examined the accuracy improvement of N-NOSE method by using two types of dilutions, 10-fold and 100-fold. We have conducted N-NOSE tests with urine samples from 32 cancer patients (esophageal, gastric, colorectal, gallbladder, cholangiocarcinoma, breast, malignant lymphoma, and acute myeloid leukemia) along with 143 healthy subjects. Our data showed a significant difference in the N-NOSE at 10-fold dilution between the two groups ( p < 0.0001), with an area under the ROC curve (AUC) of 0.9188 based on receiver operating characteristic (ROC) analysis. N-NOSE index at 100-fold dilutions was also significantly different between the two groups ( p < 0.0001), with an AUC of 0.9032 based on ROC analysis. In this clinical study, we further improve N-NOSE with a combined method of two dilutions (10-fold and 100-fold) of urine samples, which results in a markedly improvement in cancer detection sensitivity of 87.5%. N-NOSE sensitivity improvement was significantly high even for early-stage cancer detection, which is in stark contrast with the sensitivity of detection using blood tumor markers (CEA, CA19-9 and CA15-3). These results strongly suggest that the N-NOSE test by this new combined method strikes a good balance between sensitivity and specificity. Graphical abstract: Image, graphical abstract